Regulatory Governance in Infrastructure Industries: Assessment and Measurement of Brazilian Regulators - Correa, Paulo; Pereira, Carlos; Mueller, Bernardo; Melo, Marcus (Washington, DC: World Bank, 2012)
The objective of this report is twofold: to provide a comprehensive assessment of the state of regulatory governance in infrastructure industries in Brazil and to suggest possible indicators for future monitoring. After the introduction, Section 2 sets up the analytical framework for the report, identifying key components of regulatory governance, namely, autonomy (political and financial), procedures for decision making, instruments (including personnel), and accountability. Section 3 assesses each of these components in practice, reporting the results of a survey with 21 regulatory agencies in Brazil, which was designed and implemented by the research team in 2005. Section 4 measures regulatory governance based on three related indexes, ranks the Brazilian regulators among themselves, and compares the proposed indexes with two other indicators available in the literature. Section 5 presents the conclusions.